A privacidade do consumidor e a responsabilidade da empresa no espaço virtual: uma análise sob a ótica da eficácia direitos fundamentais nas relações privadas e da funcionalização do direito na responsabilidade da empresa - Gaspar, Gisele de Lourdes Friso Santos (2014)
This research aims to study the fundamental right to privacy in cyberspace, especially in consumer relations. It analyzes the effectiveness of fundamental rights in relations between individuals and the social function of company liability that is related of off-balance sheet consumer detriment. This analysis is made from punitive damages perspective. The traditional point of view states that fundamental rights are effective only in opposition to the State. However, from the 1950s this view has changed, going to check the effectiveness of these rights in relations between individuals. From another hand, the phenomenon of functionalism of the law has been growth, since the institutes of law are seen today not only by their structure but by their external relationship. By merging of these two current law visions it is possible to notice that the liability has a social function - especially when facing injuries to the right to privacy of the consumer, which is the vulnerable part of the legal relationship. The Internet revolution promoted in society is well known as well as the way people exchange information and data, facilitating communication. However, in the same way it has facilitated the relationships between people, it caused problems not previously encountered such as high privacy exposure of the consumers. The high growth electronic commerce, in larger proportions than the old means of trade, also caused the multiple problems, especially in how consumer data is protected (or exposed) in cyberspace. Due to these issues, the challenges of this research is to reconcile the right to privacy in cyberspace consumer relations as well as to determine, in accordance with current legislation, the corporate responsibility regarding the safety of consumer data. In case of injury to the consumer, this work analyses how the social function of civil liability – as a negative sanction - is able to generate positive behavioral changes, especially focused to prevent further injury.